Skipped-Generation Families: Economic Happiness in Rural North-Eastern Thailand - Wattanachai Kwalamthan; Dusadee Ayuwat; Wanichcha Narongchai (Universitas Muhammadiyah Sidoarjo, 2018)
This paper investigates economic happiness of skipped-generation families in rural north-eastern Thailand. The qualitative methodological approach was implemented in the study. Data collection was conducted in April - May 2018 and in-depth interview was used as a research instrument to collect data from two groups of key informants, including 1) community leaders, community seniors, and community commitees, In total eight persons, and 2) skipped-generation families living in a rural north-eastern region of Thailand, in total twenty families. Data analysis was done by the content analysis method. The study indicated that skipped-generation families are the familes with grandparents and grandchildren living together. Most families have an agricultural occupation, because they have a lot of land by inheritance and divided into two parts: housing and farming. Mostly agricultural income by sugar canes and farming can earn 2,400 USD per year. Moreover, remittances from international migrant only 450 USD per month is spent on family expenses and education of grandchildren. Some families do not have enoughmoney to invest in farming in the next year, and they have a lot more debt than 3,000 USD from a migrant who goes to work abroad. However, skipped-generation families have a perception of economic happiness "An empty hand is no lure for a hawk, no man is happy who does not think himself so" So, skipped-generation families must take this view to manage the economic situation of the family, even though the incomes are insuf-ficient to cover their living and lack of labor due to migrant workers going to work abroad. This affects the economic happiness of skipped-generation families to sustain their living in a rural society.SKIPPED-GENERATION FAMILIES:Economic Happiness in Rural North-Eastern Thailand